RISIKO INVESTASI DAN TINGKAT RETURN SAHAM MENGGUNAKAN CAPITAL ASSET PRICING MODEL PADA PERUSAHAAN TELEKOMUNIKASI - Jusriana, Sitti; Suhendra, Suhendra; Murniati, Murniati (Patria Artha Journal of Accounting dan Financial Reporting, 2025)
This research aims to assess the investment risk and rate of return on shares of telecommunications companies listed on the Indonesia Stock Exchange (BEI) for the 2021-2023 period using the Capital Asset Pricing Model (CAPM) method. The type of research used in this research is descriptive with a quantitative approach. The data used is adjusted monthly stock closing price data, monthly market closing prices and BI-Rate interest rates during the period February 2021- December 2023. The data analysis method used is the Capital Asset Pricing Model method. The results of the study found 12 telecommunications company stocks for the 2021-2023 period that had positive returns, namely TLKM, TBIG, ISAT, EXCL, BALI, LINK, IBST, KBLV, GHON, GOLD, LCKM, and SUPR and 2 telecommunications company stocks that had high investment risks, namely PT. Solusi Tunas Pratama Tbk (SUPR) and PT. Inti Bangun Sejahtera Tbk (IBST). For investors who have a risk seeker appetite in investing, it is advisable to choose stocks of companies that have a beta β 1 and investors are advised to avoid companies that have a negative expected return.